Methodology of teaching engineering graphics through an animated electronic textbook - Sadykova, Zhanna; Tuleuov, Galymzhan (Рroblems of engineering and professional education, 2022)
This article describes the electronic textbook "Engineering graphics with animated drawings". In the electronic textbook such topics as: video content creation, in other words, it is the content of the electronic textbook, video material; means of self-control; final management. Also it is told about how to develop the electronic textbook for training of students of architecturally-building faculty, discipline "Engineering graphics"